2016
DOI: 10.1016/j.biopsych.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Cortex Stimulation Reduces Vigilance to Threat: Implications for the Treatment of Depression and Anxiety

Abstract: Our findings provide the first experimental evidence that modulating activity in the DLPFC reduces vigilance to threatening stimuli. This significant reduction in fear vigilance is similar to that seen with anxiolytic treatments in the same cognitive paradigm. The finding that DLPFC tDCS acutely alters the processing of threatening information suggests a potential cognitive mechanism that could underwrite treatment effects in clinical populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 52 publications
7
92
0
2
Order By: Relevance
“…Importantly, similar stimulation had no effect on participants' mood. A single session of tDCS over the DLPFC also reduced attentional vigilance to fearful faces [71]. Similar results have been found in depressed populations: depressed patients were slower to name the colours of negative words than positive words in an emotional Stroop task; however, a single session of tDCS abolished this effect, reducing response times to negative words [72].…”
Section: Converging Evidence For the Neurocognitive Modelsupporting
confidence: 74%
“…Importantly, similar stimulation had no effect on participants' mood. A single session of tDCS over the DLPFC also reduced attentional vigilance to fearful faces [71]. Similar results have been found in depressed populations: depressed patients were slower to name the colours of negative words than positive words in an emotional Stroop task; however, a single session of tDCS abolished this effect, reducing response times to negative words [72].…”
Section: Converging Evidence For the Neurocognitive Modelsupporting
confidence: 74%
“…There are several important differences to note between our study and the studies cited above [19,20,45,46]. First, prior studies aimed to stimulate the dlPFC, whereas we aimed to stimulate the vmPFC because of its role in extinction learning.…”
Section: Discussionmentioning
confidence: 91%
“…Further support for the ability of tDCS to influence threat processing comes from two recent studies. Ironside et al [45] demonstrated that 20 minutes of 2 mA anodal left dlPFC - cathodal right dlPFC tDCS reduced threat sensitivity as measured with a short duration (100 ms) dot-probe task to fearful faces. A second study by Clarke et al [46] reported that 1 mA anodal left dlPFC tDCS for about 17 minutes enhanced attentional threat bias consistent with the direction of attention (toward or away).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, one cannot draw definitive conclusions of whether the greater dlPFC function in the BI group for the incongruent-versus-congruent contrast modulates threat vigilance or disengagement. Additionally, while tDCS stimulation applied to the bilateral dlPFC reduced AB to fear faces in healthy adults (Ironside et al, 2015), the causal relation between dlPFC activation and specific component of AB remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the dorsolateral PFC (dlPFC) is implicated in ongoing maintenance of executive control, such as trial-by-trial voluntary attention allocation to support task-required performance in the presence of threat-related distractors (Bishop, 2008; 2009; Luks et al, 2007). Emerging research using transcranial direct current stimulation (tDCS) to increase excitability of the dlPFC suggests that dlPFC activity casually influences threat-related AB, likely by modulating attention to salient stimuli (Clarke et al, 2014; Ironside et al, 2015). …”
Section: Introductionmentioning
confidence: 99%